Effect of Decompression on Jaw Cystic Lesions Based on Three-Dimensional Volumetric Analysis - Kwon, Yeh-Jin (Medicina (Kaunas), 2020)
Background and objectives: This study aimed to evaluate the effectiveness of decompression on jaw cysts according to various parameters by volumetric analysis using three-dimensional computed tomography. Materials and methods: Fifty patients who underwent surgical decompression of the jaw cystic lesion were selected, and their preoperative and postoperative computed tomography results between 3 and 27 months were collected. Volumetric analysis was performed to evaluate any differences in the rate of volumetric change according to the sex, age, initial volume of the lesion, duration, location of the lesion, tooth extraction, expansion of the cortical layer, and pathological diagnosis. Multiple linear regression and generalised linear mixed models were used for statistical analyses. Results: The mean reduction rate among all patients was 54.68%. Multiple linear regression analysis revealed that higher reduction rates were associated with a long decompression period, young patient age, and location of the cyst in the posterior maxilla. Generalised linear mixed models revealed that higher reduction rates were associated with a long decompression period and young patient age. Conclusions: Decompression was an effective treatment for reducing the cyst size in all patients. Its effectiveness increased with a long treatment duration, young patient age, and cyst location in the posterior maxilla three-dimensionally.